2020
DOI: 10.1073/pnas.2009899117
|View full text |Cite
|
Sign up to set email alerts
|

Targeted CRISPR screening identifies PRMT5 as synthetic lethality combinatorial target with gemcitabine in pancreatic cancer cells

Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains one of the most challenging cancers to treat. Due to the asymptomatic nature of the disease and lack of curative treatment modalities, the 5-y survival rate of PDAC patients is one of the lowest of any cancer type. The recurrent genetic alterations in PDAC are yet to be targeted. Therefore, identification of effective drug combinations is desperately needed. Here, we performed an in vivo CRISPR screen in an orthotopic patient-derived xenograft (PDX) model to iden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 55 publications
(42 reference statements)
0
42
0
Order By: Relevance
“…As previously mentioned, epigenetic factors can also contribute to chemotherapy resistance. To investigate the role of genes involved in epigenetic control of chromatin regulation, Wei et al conducted a CRISPR/Cas knockout screen and found the protein arginine methyltransferase gene 5 (PRMT5) to act as a synthetic lethal with gemcitabine in a patient-derived pancreatic cancer cell line [ 192 ]. PRMT5 is implicated in several functions, including genome organization, transcription, cell cycle, and spliceosome assembly.…”
Section: Mode Of Action Resistance Mechanisms and Vulnerabilitiesmentioning
confidence: 99%
“…As previously mentioned, epigenetic factors can also contribute to chemotherapy resistance. To investigate the role of genes involved in epigenetic control of chromatin regulation, Wei et al conducted a CRISPR/Cas knockout screen and found the protein arginine methyltransferase gene 5 (PRMT5) to act as a synthetic lethal with gemcitabine in a patient-derived pancreatic cancer cell line [ 192 ]. PRMT5 is implicated in several functions, including genome organization, transcription, cell cycle, and spliceosome assembly.…”
Section: Mode Of Action Resistance Mechanisms and Vulnerabilitiesmentioning
confidence: 99%
“…CRISPR-Cas9 gene editing has the potential to permanently disrupt tumor survival genes, which could supersede current limitations and pitfalls of traditional therapies [ 226 ]. Several companies are currently developing CRISPR–Cas9 therapeutics, but development of safe and efficient delivery modes remains a need for CRISPR-based therapies to be utilized in clinical applications.…”
Section: Applications Of Nanotechnology In Cancer Therapeuticsmentioning
confidence: 99%
“…94 95 Wei et al used in vivo CRISPR gene knockout screening in PDX mice to identify effective lethal drug combinations that synergize with GEM for treating PDAC. 96 Using a clinically relevant PDX model of PDAC with a patient tumor being propagated within the pancreas of athymic nude mice, they screened for chromatin regulators whose depletion may create conditional lethality with GEM. They found that inhibition of the protein PRMT5 led to synergistic vulnerability of PDAC cells to GEM.…”
Section: Gemcitabine Resistance and Xenograft Modelsmentioning
confidence: 99%
“…This study suggests that GEM treatment combined with inhibition of PRMT5 will have stronger effects and selectivity towards PDAC. 96…”
Section: Gemcitabine Resistance and Xenograft Modelsmentioning
confidence: 99%